2018
DOI: 10.1177/2516043518791051
|View full text |Cite
|
Sign up to set email alerts
|

The role of the patient in patient safety: What can we learn from healthcare’s history?

Abstract: Many nations, healthcare organizations and interest groups are addressing the question of how patients can best be involved in designing and executing patient safety policy. Looking back at how patient engagement has developed in healthcare, we can draw lessons on how to engage patients in patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…1,2 Physicians are encouraged to see themselves as coaches and partners, rather than the sole authority for patients' care. 3,4 This approach produces more cohesive sharing of information, keeping patients and physicians more knowledgeable and capable of making informed, joint decisions. 5,6 Prior research has identified multiple reasons for differences in opinion regarding treatment decisions between patients and their health care providers (HCPs).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Physicians are encouraged to see themselves as coaches and partners, rather than the sole authority for patients' care. 3,4 This approach produces more cohesive sharing of information, keeping patients and physicians more knowledgeable and capable of making informed, joint decisions. 5,6 Prior research has identified multiple reasons for differences in opinion regarding treatment decisions between patients and their health care providers (HCPs).…”
Section: Introductionmentioning
confidence: 99%
“…Liestikow recalls the days before patient safety was discussed openly, before there was even a word in Dutch for patient safety. 5 He reminds us of the central importance of involving patients in designing safer systems of care. However, he cautions that success in doing this will require changing the culture of health care so that patients can work alongside professionals as members of the team.…”
mentioning
confidence: 99%